Research on the Connecting Rod Trajectory of Transmission Mechanism of Electric Car Door Lock - Yan Wang; Lubin Hang; Zhe Liu; Yong Chen; Siling Wang; Qiansheng Wang; Mingyuan Wang; Lele Bai (Jixie chuandong)
The automobile door lock is an important accessory for the car body， and its operability and reliability are related to the safety and performance of the car. Aiming at the new requirements of the new car door opening function in the future， the existing car side door lock is taken as the research object， and a transmission kinematic chain that can realize the electric unlocking function is proposed. Aiming at the problem that the connecting rod transmission mechanism in the electric opening movement chain is matched with the rack drive during the unlocking movement， the desired trajectory of the theoretical contact point is a smooth curve as the target. Based on the single open chain method， a kinematic equation system with decoupling and descending characteristics is constructed. The continuous-optimization method is adopted， and considering the conditions of stable operation and reasonable size， the solution output point of the connecting rod meets the optimal size of the desired trajectory， which provides a reference for the development of the new automobile door lock motion chain.